Concepts and images of extremism and extremism and the degree of observance of prevention in the curriculum of Islamic education in the upper stage - Abu Darwish, Yanal At- Allah (Journal of Educational and Psychological Sciences, 2019)
This study aimed to evaluate how much the "Islamic education subject" is consisting of the standards of protecting student from extremism and inflexibility by answering this study main question: What are protecting student standards from extremism, and the level of considering it in "Islamic education subject" for the low, high, and secondary levels? This study was focusing on the" Islamic education subject" from 4th grade to 12th grade, the results showed that the subject has consisted many standards and tools that participate in student protection from extremism and inflexibility excepting the standard of warning youth From make inroads upon king and his capacities and the standard of clarifying of "TAKFEER dangers" and its bad consequences on society. Researcher recommended enriching this standard in the subject and the exploitation of the process of subject that will carried out by the Ministry of Education in the coming period.